2016
DOI: 10.1021/acs.jpca.6b07465
|View full text |Cite
|
Sign up to set email alerts
|

Ion–Radical Pair Separation in Larger Oxidized Water Clusters, (H2O)+n=6–21

Abstract: The structures, properties, and spectroscopic signatures of oxidized water clusters,(H2O)+ n=6–21, are examined in this work, to provide fundamental insight into renewable energy and radiological processes. Computational quantum chemistry approaches are employed to sample cluster morphologies, yielding hundreds of low-lying isomers with low barriers to interconversion. The ion–radical pair-separation trend, however, which was observed in previous computational studies and in small-cluster spectroscopy experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 85 publications
(131 reference statements)
3
18
0
Order By: Relevance
“…The detailed, inner-sphere redox mechanisms of many of these catalysts remain experimental challenges, however, which hampers further catalyst development. Recently, our research group has provided detailed computational analyses of the first oxidation step in bare water, including structures and spectra of (H 2 O) 2 + , (H 2 O) 1–5 + , and (H 2 O) 6–21 + . In addition to explaining the unique vibrational signatures of the initially formed ion-radical contact pair (H 3 O + ···OH • ), these studies and others demonstrated a propensity for ion-radical pair separation for n ≥ 5, which continues through n = 21 (and likely beyond).…”
Section: Introductionmentioning
confidence: 97%
“…The detailed, inner-sphere redox mechanisms of many of these catalysts remain experimental challenges, however, which hampers further catalyst development. Recently, our research group has provided detailed computational analyses of the first oxidation step in bare water, including structures and spectra of (H 2 O) 2 + , (H 2 O) 1–5 + , and (H 2 O) 6–21 + . In addition to explaining the unique vibrational signatures of the initially formed ion-radical contact pair (H 3 O + ···OH • ), these studies and others demonstrated a propensity for ion-radical pair separation for n ≥ 5, which continues through n = 21 (and likely beyond).…”
Section: Introductionmentioning
confidence: 97%
“…Ionized water clusters, normalH2On+, have been of remarkable interest due to their crucial roles in many chemical and biological processes, such as catalytic chemistry, radiotherapy, and the energy relaxation of photoexcited DNA base pairs . Small cationic water clusters normalH2On+, n = 2 to 6 serve as reasonable models for understanding the nature of the ionized water.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,16 In this framework, theoretical studies are mostly limited to small clusters. 12,15,[17][18][19][20][21][22][23][24][25][26] In particular, the water dimer has been largely investigated, as the simplest model to study the water cation and its reactivity. 15,17,18,21,25,26 Studies based on coupled-cluster theory have shown that, upon injection of the hole in the dimer, proton transfer occurs within 50 fs for ionization to the electronic ground state of H 2 O •+ .…”
Section: Introductionmentioning
confidence: 99%
“…19,22 However, upon increasing the size of the cluster to more than four molecules, a different mechanism has become apparent, in which the solvation of the hydronium cation becomes the dominant driving force of the reaction. 23,24 In particular, the study of clusters up to 21 water molecules indicates that the separation between the hydroxyl radical and the hydronium cation is fundamental for the stability of the system, as these two moieties are found to be at the opposite ends of the clusters upon relaxation of the ionized system. 24 Only few ab initio simulations have been performed accounting explicitly for the molecular liquid, and the effect of using approximated density functionals 27 has poorly been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation